1981
DOI: 10.1063/1.441661
|View full text |Cite
|
Sign up to set email alerts
|

Interpretations of XeI and XeBr bound–free emission spectra and reactive quenching of Xe(3P2) atoms by bromine and iodine containing molecules

Abstract: Reactive quenching studies of Xe (6s,3 P 2) metastable atoms by chlorine containing molecules

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 47 publications
4
52
0
Order By: Relevance
“…In addition to the studies already discussed in some detail, there has been a considerable effort invested in understanding the bound-free B→X emission of XeBr observed under conditions where a large number of emitting ͑Ј, JЈ͒ levels contribute to the spectra, e.g., low-pressure flow-discharge, 34 resonance-sensitization, 12 and beam-gas experiments. 14 The spectra observed in such experiments often involve quite high Ј levels having wave functions that extend over a large range of R. Accordingly, simulating the B→X spectra requires information about not only the potentials but also the transition moment function ͑which varies too slowly with R to be of importance in the kind of trial- 41, after adjustment of the latter's internuclear distance R e to match observed intensities.…”
Section: Other Workmentioning
confidence: 98%
“…In addition to the studies already discussed in some detail, there has been a considerable effort invested in understanding the bound-free B→X emission of XeBr observed under conditions where a large number of emitting ͑Ј, JЈ͒ levels contribute to the spectra, e.g., low-pressure flow-discharge, 34 resonance-sensitization, 12 and beam-gas experiments. 14 The spectra observed in such experiments often involve quite high Ј levels having wave functions that extend over a large range of R. Accordingly, simulating the B→X spectra requires information about not only the potentials but also the transition moment function ͑which varies too slowly with R to be of importance in the kind of trial- 41, after adjustment of the latter's internuclear distance R e to match observed intensities.…”
Section: Other Workmentioning
confidence: 98%
“…22 Unfortunately, we cannot precisely determine the branching ratio ⌫ ͑B/C͒ in the present study. However, we can roughly estimate an analogous branching ratio of ⌫͑B / C͒ϳ1.5Ϯ 0.3 according to both the observed emission intensity ratio between the XeBr ‫ء‬ ͑B, C͒ channels through the bandpass filters at the random orientation condition and the transmittance data for the bandpass filters if we assume the same XeBr ‫ء‬ emission spectrum in Ref.…”
Section: Methodsmentioning
confidence: 97%
“…However, we can roughly estimate an analogous branching ratio of ⌫͑B / C͒ϳ1.5Ϯ 0.3 according to both the observed emission intensity ratio between the XeBr ‫ء‬ ͑B, C͒ channels through the bandpass filters at the random orientation condition and the transmittance data for the bandpass filters if we assume the same XeBr ‫ء‬ emission spectrum in Ref. 22 for the present study. It is expected that the difference in the experimental condition with the flowing afterglow gives little influence at least on the branching ratio ⌫ ͑B/C͒.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations